THE ROLE OF CONTEXT IN ACHIEVING NATURALNESS IN TRANSLATION - Muxitdinovna, Ashrapova Nargiza (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study aims to examine how different dimensions of context—linguistic, situational, cultural, and discourse—contribute to achieving naturalness in translation and maintaining fidelity to meaning. Method: Employing a mixed-method approach, the research integrates a multi-textual corpus analysis of annotated source and target texts with translator think-aloud protocols and target reader evaluations to explore how translators utilize contextual cues in rendering natural translations. Results: The findings reveal that perceived naturalness significantly improves when translators effectively employ discourse cues, cultural presuppositions, referential coherence, and pragmatic implicature. Conversely, inadequate contextual grounding leads to translationese, awkward phrasing, and register disharmony. The study further proposes a context-aware translation model incorporating pre-translation contextual analysis, post-edition contextual tuning, and dynamic reformulation. Novelty: This research introduces an integrated framework for evaluating and enhancing contextual sensitivity in translation processes, offering theoretical and practical contributions to translator training, translation assessment, and the development of context-aware machine translation systems.